Pengembangan Multimedia Pembelajaran Tematik Berbasis Powerpoint Interaktif Kelas V Sekolah Dasar - Anam, Yusuf Syaiful (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to identify the feasibility of developing interactive powerpoint-based learning multimedia products for integrative thematic learning theme 1 sub-theme 2 class V SD/MI and identify the attractiveness of developing interactive PowerPoint-based learning multimedia products for integrative thematic learningtheme 1 sub-theme 2 class V SD/MI. To achieve the research objectives, researchers used the Research and Development (RnD) method with the Borg and Gall development model at level I. The development steps at level I include: identifying potentials and problems, studying literature and gathering information, product design, design validation and product improvement if needed. Researchers also added one more step to find out the response of students or user experience when using the product. The results of this study obtained: (1) validation test from two material experts an average score of 4.2 with an eligibility percentage of 84.4% in the